(untitled) (Experimental biology, 2020)
The article presents the results of field studies in 2019 in the Charyn GNPP. As a result of the studies, 65 species of half-winged from 10 families were identified: Nabidae (8 species), Anthocoridae (9 species), Reduviidae (3 species), Miridae (24 species), Aradidae (2 species), Lygaeidae (1 species), Coreidae ( 2 species), Tingidae (3 species), Acanthosomatidae (4 species), Pentatomidae (10 species). According to trophic specialization, zoophages (29 species), zoophytophages (11 species), phytophages (23 species) and mycetophages (2 species) are distinguished. By the number of generations per year, they are divided into 4 groups: monovoltaic (44 species), bivoltine (11 species), polyvoltine (7 species), acyclic (2 species), the number of generations is unknown in 1 species. The following ecological groups of species were identified: mesophiles (98%), xerophiles (2%). Among arboreal semi-winged animals of the Charyn GNPP, 36 species (56%) winter in the adult stage, 3 species (4%) in the adult and larva stages, -2 species (3%) in the adult stage, and 24 species in the egg stage (37%). 2 species are included in the Red Book of the Almaty region: Arma custos (Fabricius, 1794) and Zicrona caerulea (Linnaeus, 1758). Key words: dendrobiontic semi-rigid winged animals, Charyn State National Natural Park, South-East Kazakhstan.